2009
DOI: 10.6090/jarq.43.255
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Genes and Selection DNA Markers for Blast Disease in Rice (Oryza sativa L.)

Abstract: Blast is a serious disease caused by a fungal pathogen Pyricularia oryzae Cavara of rice (Oryza sativa L.). The use of resistant varieties is considered one of the most efficient ways of crop protection from the disease. In addition to a large amount of information accumulated during the long history of genetic studies on resistance to rice blast, recent progress in rice genomics has enabled us to use DNA markers for breeding the resistant varieties by marker assisted selection (MAS). In this report, we summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 91 publications
2
47
0
4
Order By: Relevance
“…The reaction of the pyramided lines to almost all isolates can be explained by the additive effect of QTLs on chromosomes 1, 2, 11 and 12 (Figure 3, Tables 2 and 3). Similarly to the results reported by Koide et al (2009), it was found that there was no reduction in the resistance caused by combining the resistance QTLs. This suggests that the pyramiding of QTLs is potentially useful for improving the blast resistance of RD6.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The reaction of the pyramided lines to almost all isolates can be explained by the additive effect of QTLs on chromosomes 1, 2, 11 and 12 (Figure 3, Tables 2 and 3). Similarly to the results reported by Koide et al (2009), it was found that there was no reduction in the resistance caused by combining the resistance QTLs. This suggests that the pyramiding of QTLs is potentially useful for improving the blast resistance of RD6.…”
Section: Discussionsupporting
confidence: 69%
“…However, the use of a single QTL as a source of resistance may be more easily overcome by the pathogen, which can be explained by the gene-for-gene theory (Flor 1971). Moreover, the high genetic variation in the blast fungus may be the main reason for numerous resistance genes having evolved and been identified in rice (Koide et al 2009). In this study, there were no parents or breeding lines with resistance to the THL185 isolate.…”
Section: Discussionmentioning
confidence: 99%
“…According to the report of Singh et al (2015), several genes for blast resistance were found and effectively used to control rice blast disease in rice breeding and genetic studies (Chen et al 2005;Ballini et al 2008;Koide et al 2009), and many blast resistant varieties have been developed. We used three major rice blast resistant genes, Pib, Pi-ta, and Pi-5 to confirm the distribution of resistance genes for improving rice blast resistance and multiple-resistance efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…For several decades, several genes of blast resistance were found that are effectively used to control rice blast disease in rice breeding and genetic studies (Chen et al, 2005;Ballini et al, 2008;Koide et al, 2009;McCouch et al, 1994 Piz genes in the tested rice germplasm, respectively. The previous studies described that the Pik-m of three Pik locus on chromosome 11 confer high and stable resistance to many…”
Section: Genetic Statistics and Similarity In Korean Landracesmentioning
confidence: 99%
“…Since then, the inheritance of resistance has been extensively studied, and over 70 major R genes have now been reported (Chen et al, 2005;Ballini et al, 2008;Koide et al, 2009). During the last few years, considerable progress has been made to understand molecular mechanisms of M. grisea infection to rice plants and rice blast R genes [Pit, Pib, Piz, Pik, Pik-m/Pik-p, Pita/Pita-2 (Hayashi et al, 2006), Piz-t (Hayashi et al, 2004;Zhou et al, 2006), Pi-d(t)2 (Chen et al, 2004), Pii (Jeon et al, 2003), Pik-m (Zhai et al, 2011), Pi39 , Pita (Jia et al, 2002 andJia et al, 2004), Pi9 , Pid2 (Chen et al, 2006), Pi2 , Pi36 , Pi37 , Pi5 (Lee et al, 2009) and Pi3 (Shang et al, 2009)] have been identified and characterized via map-based cloning or chromosome walking.…”
Section: Introductionmentioning
confidence: 99%